Metabolic syndrome and heart failure: mechanism and management - Purwowiyoto, Sidhi Laksono; Prawara, Ananta Siddhi (Medicine and Pharmacy Reports, 2021)
Heart failure (HF) and metabolic syndrome (MetS) are syndromes that affect a large proportion of the world population. MetS is known to be one of the risk factors of HF, and it can also act as comorbidity in HF. This review aims to further discuss the mechanism of MetS in causing HF, the management of MetS in order to prevent HF, and the management of MetS in HF patients. Visceral adiposity is the primary trigger of MetS which is followed by chronic inflammation, insulin resistance, and neurohormonal activation. All the mechanisms causing MetS play also an important role in the progression of HF. The MetS approach can be achieved by managing its components according to the current guidelines and careful management of MetS should be done in patients with HF. MetS is closely related to the progression of HF so that comprehensive management which involves a multidisciplinary team is necessary for managing patients with metabolic syndrome and heart failure.